2021
DOI: 10.1155/2021/8851884
|View full text |Cite
|
Sign up to set email alerts
|

Ligustrum japonicum Thunb. Fruits Exert Antiosteoporotic Properties in Bone Marrow-Derived Mesenchymal Stromal Cells via Regulation of Adipocyte and Osteoblast Differentiation

Abstract: Ligustrum japonicum fruits have been used as a part of traditional medicinal practices and supplements in Korea and Japan. It has been reported to possess various bioactivities, but its antiosteoporotic potential and active substances have not been reported yet. The present study followed an ALP activity and lipid accumulation-guided screening of L. japonicum fruits for antiosteoporotic compounds and isolated salidroside as an active compound. Antiosteoporotic effects of L. japonicum fruits and salidroside wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In the early stage, MSCs, as multipotential progenitor cells, are delicately balanced for their terminal adipo-osteogenic differentiation commitment[ 49 - 51 ]. It has also been reported that this decision process of MSCs is competing and reciprocal, and is precisely achieved by a variety of critical and external cues, including phytocannabinoids, conjugated linoleic acid, calcium, and chemical, physical and biological factors[ 52 - 58 ]. Many investigations in vitro had demonstrated that deficient calcium exposure inhibited osteogenesis[ 59 - 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage, MSCs, as multipotential progenitor cells, are delicately balanced for their terminal adipo-osteogenic differentiation commitment[ 49 - 51 ]. It has also been reported that this decision process of MSCs is competing and reciprocal, and is precisely achieved by a variety of critical and external cues, including phytocannabinoids, conjugated linoleic acid, calcium, and chemical, physical and biological factors[ 52 - 58 ]. Many investigations in vitro had demonstrated that deficient calcium exposure inhibited osteogenesis[ 59 - 61 ].…”
Section: Discussionmentioning
confidence: 99%